Paradoxes of the Creative City. Contested Territories and Creative Upgrading - the Case of Berlin, Germany - Hesse, Markus; Lange, Bastian (DIE ERDE – Journal of the Geographical Society of Berlin, 2013)
The paper emphasises the rising interest in creativity as a consequence of late-modern cultural economic change and as a means of urban regeneration. Based on a critical appraisal of related strategies, the case of Berlin, the German capital, is investigated empirically. Against the background of so-called “paradoxes” of creativity, two local areas of conflict are being discussed in more detail: first a riverside area that is under pressure of globalisation and gentrification (“Mediaspree”), second an inner-city street corridor (“°m-street”) with creative occupation that currently suffers from urban degradation. The two cases demonstrate the different ways in which the new cultural economy is going to be spatialised. In this context, the paper draws some general conclusions on urban governance for the creative city.